2007
DOI: 10.1002/evan.20143
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the nose and nasal skeleton in primates

Abstract: One traditional diagnostic feature of the Order Primates is a decreased emphasis on olfaction.1, 2 Some authors attribute this feature only to tarsiers and anthropoids, either through convergence or as a common feature of haplorhines.2–4 Other authors de‐emphasize olfaction relative to vision,5–7 which does not necessarily denote olfactory reduction per se. There are lengthy roots to this discussion. The importance of the sense of smell to at least some primates, humans in particular, has long been viewed as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(77 citation statements)
references
References 94 publications
(181 reference statements)
1
75
0
1
Order By: Relevance
“…Primates are characterized by a reduction of the nasal fossa relative to other mammals, although the extent varies greatly across the order (Smith et al, 2007b). Because of varying degrees of orbital convergence toward the midline, the FR is nearly or completely obliterated in haplorhines (Cartmill, 1970;Smith et al, 2007b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Primates are characterized by a reduction of the nasal fossa relative to other mammals, although the extent varies greatly across the order (Smith et al, 2007b). Because of varying degrees of orbital convergence toward the midline, the FR is nearly or completely obliterated in haplorhines (Cartmill, 1970;Smith et al, 2007b).…”
Section: Resultsmentioning
confidence: 99%
“…Because of varying degrees of orbital convergence toward the midline, the FR is nearly or completely obliterated in haplorhines (Cartmill, 1970;Smith et al, 2007b). It has been observed that the FR may also be somewhat ''compressed'' by enlarged orbits in at least some strepsirrhines compared with most other mammals (Smith and Rossie, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FR, opening to frontal recess; I-IV, ethmoturbinals I through IV; MarT, marginoturbinal; MT, maxilloturbinal; N, nasal bone; ND, nasopharyngeal duct; NT, nasoturbinal; OR, olfactory recess; P, osseous palate; Pmx, premaxillary bone; SP, soft palate; TL, transverse lamina. Figure 1a the vomeronasal organ in Microcebus has been carefully described in previous publications (Schilling, 1970;Smith et al, 2007a), and will not be considered further.…”
Section: Structural Relations and Terminology Of Nose And Nasal Fossamentioning
confidence: 99%
“…In addition, the terminology used to describe structures varies greatly. These factors are limitations in the endeavor to understand functional specializations and the evolutionary modifications of the nasal fossa in different mammalian taxa, particularly in groups with highly diverse nasal morphology (Smith et al, 2004;Smith and Rossie, 2006;Smith et al, 2007a).…”
mentioning
confidence: 99%